Dominance of hepatitis C virus (HCV) is associated with lower quantitative hepatitis B surface antigen and higher serum interferon-γ-induced protein 10 levels in HBV/HCV-coinfected patients. (July 2015) - Wiegand, S.B.; Jaroszewicz, J.; Potthoff, A.; Höner zu Siederdissen, C.; Maasoumy, B.; Deterding, K.; Manns, M.P.; Wedemeyer, H.; Cornberg, M.
Abstract: Different viral dominance patterns have been documented in coinfection with hepatitis B virus (HBV) and hepatitis C virus (HCV) based on HBV DNA and HCV RNA quantification. In most cases, HCV is dominant and suppresses HBV replication. In vitro studies revealed that there is most probably no direct interference between HBV and HCV replication. We hypothesized that indirect mechanisms mediated by host immune responses might be responsible for the different dominance patterns. In this study we analysed quantitative hepatitis B surface antigen (HBsAg) as a marker for immune control of HBV and interferon γ-induced protein 10 (IP-10) as host marker for the endogenous interferon in 85 patients with HBV/HCV coinfection. Levels of HBsAg were closely associated with viral dominance patterns in 85 HBV/HCV-coinfected patients. HBsAg levels were lowest in patients with HCV dominance, even lower compared with HBV-monoinfected patients undergoing treatment with nucleos(t)ide analogues (NA) but comparable to low replicative HBsAg carriers. An increase in HCV RNA during follow up was associated with HBsAg decline. Patients with HCV dominance had significantly higher serum IP-10 levels compared with HBV-dominant patients or HBV-monoinfected patients treated with NA. Lower HBsAg and higher IP-10 levels in HCV-dominant HBV/HCV-coinfected patients suggest that HCV suppresses HBV DNA replication and also HBsAg production by immune mechanisms.